Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Đặt \(\frac{a}{b}=\frac{c}{d}=k\Rightarrow\begin{cases}a=kb\\c=kd\end{cases}\)
=> \(\frac{a^2+b^2}{c^2+d^2}=\frac{\left(kb\right)^2+b^2}{\left(kd\right)^2+d^2}=\frac{b^2\left(k^2+1\right)}{d^2\left(k^2+1\right)}=\frac{b^2}{d^2}\) (1)
\(\frac{ab}{cd}=\frac{kbb}{kdd}=\frac{k.b^2}{k.d^2}=\frac{b^2}{d^2}\) (1)
Từ (1) và (2) => \(\frac{a^2+b^2}{c^2+d^2}=\frac{ab}{cd}\)
b) Đặt \(\frac{a}{b}=\frac{b}{c}=\frac{c}{d}=k\)
Ta có: \(\frac{a^3+b^3+c^3}{b^3+c^3+d^3}=\frac{a^3}{b^3}=\frac{b^3}{c^3}=\frac{c^3}{d^3}=k^3\)
Mà: \(k^3=\frac{a}{d}\) => \(\frac{a^3+b^3+c^3}{b^3+c^3+d^3}=\frac{a}{d}\)
a)Ta có:\(\frac{a}{b}=\frac{c}{d}\Rightarrow\frac{a}{c}=\frac{b}{d}\)
\(\Rightarrow\left(\frac{a}{c}\right)^2=\left(\frac{b}{d}\right)^2=\frac{a^2}{c^2}=\frac{b^2}{d^2}=\frac{a}{c}\cdot\frac{b}{d}=\frac{ab}{cd}\)
\(\Rightarrow\frac{a^2}{c^2}=\frac{b^2}{d^2}=\frac{a^2+b^2}{c^2+d^2}=\frac{ab}{cd}\left(đpcm\right)\)
1,
\(\frac{a+2}{a-2}=\frac{b+3}{b-3}\)
<=> (a - 2)(b + 3) = (a + 2)(b - 3)
<=> ab + 3a - 2b - 6 = ab - 3a + 2b - 6
<=> 3a - 2b = -3a + 2b
<=> 6a = 4b
<=> 3a = 2b
<=> \(\frac{a}{2}=\frac{b}{3}\)(Đpcm)
2,
Có:
\(\frac{bz-cy}{a}=\frac{cx-az}{b}=\frac{ay-bx}{c}\)
\(=\frac{abz-acy}{a^2}=\frac{bcx-baz}{b^2}=\frac{cay-cbx}{c^2}\)
\(=\frac{abz-acy+bcx-baz+cay-cbx}{a^2+b^2+c^2}=0\)
=> bz - cy = 0
=> bz = cy
=> \(\frac{b}{y}=\frac{c}{z}\)(1)
=> cx - az = 0
=> cx = az
=> \(\frac{c}{z}=\frac{a}{x}\)(2)
Từ (1) và (2)
=> \(\frac{a}{x}=\frac{b}{y}=\frac{c}{z}\)(Đpcm)
#)Giải : (Bài này ez mak :v)
\(\frac{a+2}{a-2}=\frac{b+3}{b-3}\)
\(\Rightarrow\left(a+2\right)\left(b-3\right)=\left(a-2\right)\left(b+3\right)\)(bước này mk làm tắt đi nhé)
\(\Rightarrow3a=2b\)
\(\Rightarrow\frac{a}{2}=\frac{b}{3}\)
\(\Rightarrowđpcm\)
Ta có: \(\frac{a+2}{a-2}=\frac{b+3}{b-3}\)
=> \(\frac{\left(a-2\right)+4}{a-2}=\frac{\left(b-3\right)+6}{b-3}\)
=> \(1+\frac{4}{a-2}=1+\frac{6}{b-3}\)
=> \(\frac{4}{a-2}=\frac{6}{b-3}\)
=> \(4\left(b-3\right)=6\left(a-2\right)\)
=> \(4b-12=6a-12\)
=> \(4b=6a\)
=> \(2b=3a\)
=> \(\frac{b}{3}=\frac{a}{2}\)
Từ \(\frac{a+2}{a-2}=\frac{b+3}{b-3}\)
<=> (a+2)(b-3) = (a-2)(b+3)
<=> ab-3a+2b-6 = ab+3a-2b-6
<=> -6a = -4b
<=> \(\frac{a}{b}=\frac{3}{2}\)
<=> \(\frac{a}{2}=\frac{b}{3}\)
Ta có:\(\frac{a+2}{a-2}=\frac{b+3}{b-3}\)
\(\Leftrightarrow\frac{a-2+4}{a-2}=\frac{b-3+6}{b-3}\)
\(\Leftrightarrow1+\frac{4}{a-2}=1+\frac{6}{b-3}\)
\(\Leftrightarrow\frac{4}{a-2}=\frac{6}{b-3}\)
\(\Leftrightarrow\frac{2}{a-2}=\frac{3}{b-3}\)
\(\Leftrightarrow\frac{a-2}{2}=\frac{b-3}{3}\)
\(\Leftrightarrow\frac{a}{2}-1=\frac{b}{3}-1\)
\(\Leftrightarrow\frac{a}{2}=\frac{b}{3}\)